Periodontal Disease as a Risk Factor for Cardiovascular Disease - A Questionnaire Survey among Physicians - Arya, Varun; Kudpi, Ramya Shenoy; Rungta, Nikita (Journal of Medicine, 2021)
Introduction: Periodontal infections have been documented to influence coronary heart diseases such as angina, myocardial infarction, atherosclerosis and other systemic conditions like stroke, diabetes mellitus and preterm low birth weight babies. Over the last two decades, several studies have reported associations between periodontitis and cardiovascular disease (CVD). The association is now a part of the dental school curriculum and periodontology. However, in contrast, this important aspect is missing in the medical school curriculum and not many physicians are aware of the role periodontal disease plays in CVD. Aim: To assess the knowledge and practices of physicians of Mangalore City, South India, on periodontal disease as a risk factor in Cardiovascular Diseases (CVD). Methodology: A questionnaire survey was carried out to assess physicians’ knowledge and practices in the city of Mangalore, South India. The physicians were divided into four groups as follows: Group I - Physicians associated with medical colleges; Group II – Sole private practitioners; Group III - Physicians associated with medical colleges and having their private practice; Group IV - Post-graduate students. A Chi-square test was applied to test the difference between knowledge and practices among the groups. Results: Out of a total of 106 physicians, 56 (52.3%) participated in the survey. Periodontal disease was considered to be a risk factor in CVD by 87.5% (n=47) respondents and 96.4% (n=54) respondents stated that bleeding/enlargement of the gingivae was a sign of periodontal infection. Only 40% (n=23) of the respondents asked about oral problems during general check-up. Conclusions: The knowledge regarding the periodontal disease as a risk factor in CVD was high, however, the application of the knowledge in routine medical check-ups was observed to be less. J MEDICINE JAN 2021; 22 (1) : 7-11